Dinâmica dos componentes do PIB brasileiro: uma análise de domínio tempo-frequência - Pinheiro Neto, Germano (2024)
Understanding the relationship between the components of national GDP expenditure is a fundamental part of macroeconomic study. The general objective of this dissertation is to explore the relationship between the components of GDP expenditure in the time-frequency domain and to obtain some stylized facts. Thus, this work investigates the relationship between the cyclical components of growth in real quarterly GDP data from Brazil between 1996 and 2023, applying continuous wavelet analysis in cross-comparisons of data, both within and between the two data sets. In this study, the cyclical components of aggregate demand and their implications on the economy were analyzed. The results indicate that the relationship between investments and imports was significant, especially in the short and medium term, highlighting the period between 2000 and 2008 when imports led cycles in phase with investments. However, this dynamic was interrupted by the subprime crisis, which shook global markets. Imports were identified as stimuli for investments, providing access to foreign resources and markets. On the other hand, the relationship between consumption and government spending proved to be stronger, with government spending leading cycles during economic slowdowns, demonstrating the importance of fiscal policies in mitigating recessions and driving growth. Regarding the dynamics between consumption and investments, it was found that in the short term, consumption preceded investments, while in the medium term, investments led cycles, indicating a dynamic interdependence between these components in the economy.